Synthesis of Knowledge on Infant Fortification Plants and the Most Commonly Used Galactogenic Plants in Niger and Their Uses in the Republic of Niger - Rahila Hama Garba; Idrissa Moussa; Hassimi Sadou; Ramona Suharoschi; Flore Depeint (Nutraceuticals)
The use of plants for therapeutic purposes is an ancestral practice that dates back to the earliest times in the history of mankind. Even today the exploitation of plants for medicinal purposes plays a big role for the communities, especially in Africa, despite advances in modern medicine. According to the World Health Organization, about 80% of the population in developing countries use plants for their primary health care. In Niger, the use of medicinal plants is a foundation of traditional medicine across all ages. It remains a very common practice, especially in rural areas. This practice concerns all ages of life, including mother–child care. In infants and young children, mothers use plants as fortifiers for their prophylactic or curative powers, or to facilitate growth and weight gain, and also to fight major causes of infant morbidity and mortality. Mothers also use medicinal plants for their galactogenic power to stimulate lactation. This is even more important in rural areas where breastfeeding is the main source of infant nutrition. Over the years, these medicinal plants have been the subject of chemical and biological investigations to back up their therapeutic potential and virtues. This study aims to summarize current knowledge on the most commonly used medicinal plants in Niger in mother–child care. This helps emphasize the validation of ancestral medicinal plants through the scientific evaluation of the bioactive components and mechanisms. Elements of sustainability are discussed in future developments.